Peran Kepala Sekolah dalam Melaksanakan Manajemen Mutu Pendidikan di MI NW Tangar Lingsar - Yon Hadi, Irwan (ARZUSIN, 2024)
As an educational leader at the unit level, the principal has a strong leadership foundation and is responsible for the success or failure of the school he supervises. Analysis of the principal's function in educational quality management, analysis of the principal's role in its implementation, and identification of elements that facilitate and hinder the implementation of educational quality management are the objectives of this study. This study is descriptive qualitative, and data analysis techniques include reduction, triangulation, presentation, and verification/conclusion. The findings of this study include (1) The Principal's Function in Organizing Educational Quality Management (a) Steps taken to improve educational quality, such as developing plans for student academic progress, building a rich learning environment in schools, fostering a leadership mindset among all academic and non-academic staff, improving learning, and supervising all academic and non-academic staff (2) The Principal's Role in Implementing Educational Quality Management (a) Making Policies on Educational Quality, (b) Tracking and Assessment, (c) Human resource development, (d) resource management, (e) stakeholder involvement and communication, (f) problem solving, and (g) empowerment of the management team, (h) Continuous Improvement The implementation of educational quality management is influenced by enabling and inhibiting factors. (a) Enabling factors include effective leadership, stakeholder involvement, sufficient resources, training and development, supportive organizational culture, collaboration and cooperation, and ongoing monitoring and evaluation. (b) barriers, such as scarce resources and an unfriendly corporate culture.